Harnessing hyaluronic acid for the treatment of osteoarthritis: A bibliometric analysis - Zhang, Jun; Lin, Miaoyuan; Huang, Yanran; Wang, Yuping; Huang, Tianji; Wu, Zhillin; Li, Zefang; Xu, Jingtao; Zhao, Runhan; Luo, Xiaoji (Frontiers in bioengineering and biotechnology, 2022)
Background: Osteoarthritis (OA) is a common disease which usually occurs in middle-aged and elderly people. Hyaluronic acid (HA) has been widely used to treat OA and related researches on the efficacy and safety of HA in the treatment of OA have been published. Therefore, the purpose of this research was to investigate the subject characteristics of harnessing HA for the treatment of OA and to analyse the relevant trends and hotspots by using a bibliometric approach. Methods: The articles published from 1 January 2002 to 31 December 2021 were searched in the Web of Science Core Collection (WoSCC) and the relevant information of HA for the treatment of OA was extracted after screening. Then, a total of 2438 publications were analysed by using Microsoft Excel, CiteSpace 5.8.R3, VOSviewer 1.6.18 and the Online Analysis Platform of Literature Metrology ( http://bibliometric.com/ ). Results: A total of 2438 articles were finally included for analysis. The number of publications increased year by year. A total of 83 coutries and 3319 institutions published 2438 manuscripts in the field of use HA for the treatment of OA. The most productive country was United States with total 689 publications and League of European Research Universities Leru (Belgium) was the leading institution with total 126 publicatios. In terms of authors, the most prominent author was KrausVB, who published 28 papers with the highest H-index (19). In addition, Osteoarthritis and Cartilage had the highest number of publications (152 articles) and the highest number of citations (6450 citations). The co-cited references analysis indicated that the article published by McAlindon in 2014 had the most highest number of citations (91co-citations). What’s more, most research hotspots focused on the efficacy and safety of HA, and regenerative medicine researches such as platelet-rich plasma (PRP) and mesenchymal stem cells (MSCs) have attracted more and more attentions of researchers. Conclusion: This study visually analyzed the historical evolution and future trends of HA for the treatment of OA, and discussed the research priorities. At present, there are still different views on the efficacy of HA for the treatment of OA. Gradually, research hotspots of this field have focused on the regenerative medicine.